Tahlil al-Akhta’ an-Nahwiyyah fi at-Ta’bir at-Tahririy fi IAIM Metro Lampung - Dian Risky Amalia; Nanda Fitriana Lukya (Postgraduate of IAIN Metro Lampung Indonesia, 2020)
The writing as a language skill is not a simple skill. However, writing skills are the most difficult language skills to master because writing is a very complex cognitive process. One of the rules of writing that should be taken into account is the writing of grammar (grammar). The purpose of this study was to determine how grammatical errors in the editorial expression of the third mannequin of the University of Islamic Knowledge Metro Lampung. Based on an analysis of the data that was conducted. Type of this research It is qualitative and descriptive the researcher used methodically, qualitative research is a process of research and understanding based on the methodology that investigates the social phenomenon and human problems. The results of the research found that there are 20 errors in the editorial expression of students of the third stage of the University of Islamic Knowledge metro Lampung with details of 5 errors in the category of al ism almarfu’ (2 errors in the mubtada’, 1 errors in the na’at, 1 errors in the‘athaf, 1 errors in the fa’il), 5 errors In the category of al ismu almanshub (2 errors in the maf’ul bih, 3 errors in the ‘athof), 10 errors in the category of al ism almajrur (4 errors in the idhafah, 1 errors in the badal, and 4 errors in the syibh aljumlah). The final result presentation result is 25% erors in the category of al ism almarfu’, 25% errors In the category of al ismu almanshub and 50% in the category of al ism almajrur. Key words: writing, grammar, error analysis